Swaying Aspects of Employee Performance (Quantitative Study of Fertilizer Sector) (Global Journal of Science Frontier Research, 2014)
Employee play vigorous role in the growth of an organization.Learning the skills is the essential process of improving performance throughout a company Training especially by involving employees in the decision-making. The purpose of this paper is to seek out the effects of influencing factors of employee's performance in fertilizer sector of D.G Khan Pakistan. With the help of influencing factors includes the training, motivation, feedback, job involvement find out most significant factor that's leads the employee performance in fertilizer sector of D.G Khan, Pakistan. In this study data was collected on primary basis through close ended questionnaires from employees of fertilizer sector of D.G Khan Pakistan. On the basis of 84 respondents results were analyzed with the help regression and correlation.Employee performance, training, motivation, feedback and job involvement were never analyzed together in previous studies. From the analysis, it was clear that above mention influencing factors play vital role in the fertilizer sector of D G Khan and it also acted as a motivational force that influences employee performance.
Keywords: Employee play vigorous role in the growth of an organizationLearning the skills is the essential process of improving performance throughout a compan